Restorative Surgery in Patients With Primary Sclerosing Cholangitis and Ulcerative Colitis Following a Colectomy. Issue 3 (16th February 2018) - Nordenvall, Caroline; Olén, Ola; Johan Nilsson, Per; Ekbom, Anders; Bottai, Matteo; Myrelid, Pär; Bergquist, Annika
Abstract: Background: Studies on surgical procedures in patients with concomitant primary sclerosing cholangitis (PSC) and ulcerative colitis (UC) have mainly been restricted to single centers. The aim was to compare surgical treatment of UC with or without PSC in a nationwide study. Methods: A cohort study including all patients diagnosed with UC between 1987 and 2014 in Sweden was undertaken. The impact of PSC on the risk of colectomy, the chance of restorative surgery, and risk of failure (presence of a stoma) following restorative surgery were estimated. Survival analyses were performed using the Kaplan-Meier method and multivariable Cox regression models. Results: Of 49 882 UC patients, 2079 had a PSC diagnosis at the end of follow-up. The risk of colectomy was unaffected by PSC diagnosis, whereas the chance of restorative surgery was elevated in PSC-UC patients (hazard ratio [HR], 1.22; 95% confidence interval [CI], 1.02–1.44). Ileorectal anastomosis (IRA) was performed in 63% of the PSC-UC patients and 43% of the non-PSC-UC-patients, and the corresponding numbers for ileal pouch anal anastomosis (IPAA) were 35% and 53%. There was no significantly increased risk of failure following restorative surgery in PSC patients (HR, 1.44; 95% CI, 0.93–2.22). In PSC-UC patients, the cumulative failure rates following an IRA at 3 and 5 years were 15% and 18%, and following an IPAA they were 11% and 18%, respectively. Conclusions: Presence of PSC is not associated with the risk of colectomy, whereas the chance of restorative surgery in PSC-UC patients is higher than in UC alone.